A New Method for Airborne Sound Detection Using Total Internal Reflection and Its Application to Microphone. (21st November 2011) - Suzuki, Yasushi; Kido, Ken'iti
Abstract : A new method for detecting the sound pressure in air, which uses the total internal reflection at the curved interface between glass and air, is proposed, and its application to microphone is discussed. The critical angle for total reflection changes by the refractive index of air, which depends on the air density. The density changes by the sound pressure. Therefore, the sound pressure is measurable by detecting the intensity of the reflected light from the total reflection area. The sound pressure sensitivity of the proposed method is investigated theoretically and experimentally. Experimental results show that the microphone using the method is feasible though its sensitivity is low in the present stage. When the sensitivity is improved dramatically for practical use, the microphone becomes very sensitive to the surrounding conditions. A method to compensate the fluctuation of atmospheric pressure or temperature is presented.